The Aesthetics of deviating of word structure of Nawzad Rafaat’s poems (Raparin Journal of Humanities (RJH), 2023)
This research entitled “The Aesthetics of deviating of word structure of Nawzad Rafaat’s poems” is a phase to display and identify the literary devices that estimate aesthetics as a criteria genre of poetry in which it reveals the beauty of poems. It is also a definite attempt to highlight the deviations made on word structure used in the poems. In addition, that demonstrates the poets’ active methods, ability, energy, conversational skills and expressions in using deviations to embody and express aesthetics in his poems.